National brands in hard discounters: Market expansion and bargaining power effects - Céline Bonnet; Zohra Bouamra-Mechemache; Gordon Klein (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
In this paper, we analyze the strategic role of the recent introduction of national brand products by hard discounters in the French market and its impact both at the retail and manufacturer levels. We use a structural econometric model of vertical relationships that takes into account the competition between both mainstream retailers and hard discounters, and between national brands and private labels. We apply this model to the French dairy dessert market, which is characterized by a high penetration of private labels and a high concentration at the manufacturer and retail levels. Using a counterfactual analysis, we show that the introduction of national brands by hard discounters does not only act as means to attract different consumer groups and extend their market share. In addition and even maybe more important, we also show that the introduction of national brands by hard discounters serves as a means to improve their bargaining positioning with respect to their private label providers.
Keywords: L11; L25; L81; M31; 330; Structural Model; Counterfactual Analysis; Hard Discount; The Role of Private Labels and National Brands